The Profile of Anti-inflammatory Activity of Syzigium Aromaticum Volatile Oil in Lotion with Variation Composition of Oleic Acid and Propylene Glycol as Enhancer - Fitriah Ardiawijianti Iriani; Nining Sugihartini; Tedjo Yuwono (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Essential oil of clove (Syzygium aromaticum) containing eugenol has an anti-inflammatory activity. The study was aimed to develop the formulation of lotion by adding of oleic acid and propylene glycol as penetration enhancer. The effect of enhancer composition was also studied. Lotion was prepared with the composition of oleic acid (AO) and propylene glycol (PG) as follow: 1:0 (FI), 0,5:0,5 (FII), 0:1 (FIII). Capacity an anti-inflammatory of formulation based on parameters of the amount of cells with COX-2 expression, the number of inflammatory cells and the epidermis thickness was evaluated using male mouse strain BALb/C induced by crotton oil as inflammatory agents. The results showed that the increasing composition propylene glycol caused the decreasing of the amount of cells with COX-2 expression (p <0.05), the inflammatory cells (P <0.05) and the epidermis thickness (p <0.05)